An urban pipeline accident model based on system engineering and game theory. (March 2020) - Xing, Jinduo; Meng, Huixing; Meng, Xiangkun
Abstract: Urban pipeline accidents are caused by complex social-technical factors, in which urban communities and pipeline systems are involved. Such accidents can thus be investigated from the viewpoint of system engineering. System-Theoretic Accident Model and Processes (STAMP) is a systemic method for safety assessment, which has been adopted in many domains. This approach can provide deep insights of accident causes by considering direct and indirect factors. Meanwhile, competition and cooperation between stakeholders in accidents are observed. Therefore, these parties can also be analyzed with the game theory. That is, stakeholders in STAMP can be regarded as players in game. The aim of this paper is to provide a new insight to analyze urban pipeline accidents by considering both STAMP and game theory. In this paper, we proposed an accident model for urban pipelines, with a case study of China-Qingdao pipeline accident occurred in 2013. We concluded that accident reasons can be investigated in-depth and lessons can be learned from analyzing causal factors by using STAMP. Based on results generated from STAMP, we applied the game theory to analyze roles that government and companies act in the China-Qingdao urban pipeline accident. The results show that current punishment and incentive systems are incomplete, lacking of the driving force and constraining force for the stakeholders involved in the accident. Highlights: We propose to analyze urban pipeline accidents by combining system engineering and game theory. Stakeholders in STAMP can be regarded as players in game. We discuss lessons learned from in-depth accident analysis with STAMP-Game model.